DAMPAK DOMINO KRISIS EUROZONE TERHADAP NEGARA ITALIA - Febi Hananaomi; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explained about the impact of the eurozone crisis domino against the Italy. The economic crisis in the eurozone caused by the domino effect in European Union countries. The crisis first emerged from the Greece which eventually spread to other European Union countries. This occurs as a result of entanglement in the geo-politics and geo-strategic. One of the countries that participated affected is Italy. Although Italy has a good achievement in economics, but in 2011 Italy was also affected by the eurozone crisis domino effect. The crisis impact on the economy and politics of the country.This research was used qualitative analysis. Theory used in this research was the theory of United State’s President, Dwight Eisenhower. According to Eisenhower in 1979, a phenomenon known as the domino by the chain changes on the basis of geo-political and geo-strategic. Because of this theory was born of geographical, then the object is the countries that are geographically close. From the description it can be seen that the eurozone crisis happened because the European region countries in the region are located geographically close to each other that causing a domino impact.Finally, this research show about eurozone crisis domino caused by geographical attachment. One of the affected country is Italy. Based on this research, it can be seen that Italy is a country that is well known on innovative business economic sector and influence on the agricultural sector and the industrial character has high competitiveness. Although many important achievement that Italy had, there currently experiencing problems in Italy's economic development because of the eurozone crisis. The crisis affected Italy both in the economy and politics.Keywords : Domino impact, Eurozone Crisis, Italy